A Practical Tax Policy to Fight Climate Change: The Utility Savings Account. (13th April 2021) - Price, Jason; Casagranda, Blake
Abstract : Underneath the labyrinth of Internal Revenue Service (IRS) tax rules is a sophisticated system designed to generate revenue for the government, redistribute wealth among US citizens, and motivate certain investment and consumer behavior. Government is empowered to choose what and how and whom to tax based on the nature and purpose of the proposed tax. In doing so, lawmakers attempt to be fair, equitable, and pro‐growth in setting tax policy. The application of tax policy to address climate change has been primarily focused on reducing the use of fossil fuels with more recent discussions considering the imposition of a tax on carbon. An alternative strategy to influence the public would be to modify the tax policy in the form of a pre‐taxable income benefit known as the Utility Savings Account (USA), where the term "Utility" includes electric, gas, heating oil, and energy efficiency and renewable energy services.